VOLUMETRY AND SURVIVAL OF NATIVE AND EXOTIC SPECIES IN THE GYPSUN POLE OF ARARIPE, PE - Bruno Coelho de Barros; José Antônio Aleixo da Silva; Rinaldo Luiz Caraciolo Ferreira; Ana Clara Moura Neves Rebouças (Ciência Florestal, 2010)
In the industrial and commercial sectors of the Araripe Region in Pernambuco, Brazil, fire wood is the used in processes of dehydration and production of gypsum with different technologies. Thus, this study aimed to find alternatives to supply the demand of firewood in the Gypsun Pole of Araripe in Pernambuco through the implementation of forest with native and exotic species. The experiment was installed at the Experimental Station of the Agronomic Institute of Pernambuco (IPA), using nine species, both native and exotic: (Imburana - Amburana cearense (Allemão) A.C. Sm.; Angico - Anadenanthera colubrina (Vell.) Brenan  var. cebil (Griseb.) Altschul; Jurema - Mimosa tenuiflora (Willd.) Poir.; Sabiá - Mimosa caesalpiniaefolia Benth.; Acácia - Senna siamea (Lam.) H.S. Irwin & Barneby; Leucena - Leucaena leucocephala (Lam.) R. de Wit.; Algaroba - Prosopis juliflora (Sw.) D.C.; Ipês - Tabebuia sp.1 e Tabebuia sp.2). The design was completely randomized with different numbers of replications. The following parameters were evaluated: volume in cubic meter (m³) and stereo meters (st) and survival. With regard to the volume in cubic meter, Sabia had the best production. The Jurema and the Sabiá were the heaviest species. In relation to survival, the Ipê 2 and the Imburana had the highest mortalities. Thus, the Sabiá and the Jurema are the species indicated for the production of wood in homogeneous commercial plantations in the Chapada Araripe in Pernambuco.